One‐pot Construction of Dibenzooxabicyclo[5.5.0]dodecanes - Hsueh, Nai‐Chen; Chen, Kuan‐Ting; Chang, Meng‐Yang (Advanced synthesis & catalysis, 2022)
Under the open‐vessel atmosphere conditions, the one‐pot synthesis of bis‐sulfonyl dibenzooxabicyclo[5.5.0]dodecanes was developed by double substitution of 1,3‐dichloroacetone with arenesulfinic acid sodium salts, and C‐ and O‐alkylation of the resulting 1,3‐bis‐sulfonylacetones with 2 equivalents of o‐bis(bromomethyl)arenes. A plausible mechanism is proposed and discussed. This high‐yielding protocol provides an intermolecular substitution and an intramolecular ring‐closure via the formations of three carbon−carbon single (C−C) bonds, two carbon−sulfur single (C−S) bonds, and one carbon−oxygen single (C−O) bond.